Breathable dustproof wall cloth and preparation method thereof

By using cotton fibers, PET fibers and modified fibers in the wall cloth, combining electrospinning method and particulate composites, a composite fiber layer is formed, and modified nanosilver is introduced into the polyurethane protective layer, which solves the problem of insufficient breathability and dust resistance of the wall cloth, and achieves the effects of high breathability, dust resistance and antibacteriality.

CN120042072AActive Publication Date: 2025-05-27ZHEJIANG YAKINO DECORATIVE MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510511030.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-05-27
Estimated Expiration
2045-04-23

AI Technical Summary

Technical Problem

The existing wall cloth has shortcomings in terms of breathability and dust resistance, and it is difficult to meet the needs of high breathability and dust resistance.

Method used

Nanofibers were prepared by electrospinning by using cotton fibers, PET fibers and modified fibers, and particle composites were introduced into the nanofibers to form a composite fiber layer. At the same time, the prepolymer formed by isocyanate and polyether glycol is reacted through chain extension and modified nanosilver, and the additive is added to obtain a polyurethane protective layer emulsion, and finally a breathable dust-proof wall cloth is prepared by thermal curing.

Benefits of technology

It improves the tensile performance and breathability of the wall cloth, while enhancing dust resistance and hydrophobicity, and improving antibacterial performance, enhancing the comprehensive practicality of the wall cloth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120042072A_ABST
    Figure CN120042072A_ABST
Patent Text Reader

Abstract

The invention relates to the field of wall cloth, in particular to breathable dustproof wall cloth and a preparation method thereof. The problem that in the prior art, wall cloth is insufficient in breathability and dustproof performance is solved. The preparation method comprises the following steps: preparing nanofibers from cotton fibers, PET fibers and modified fibers by using an electrostatic spinning method, and introducing a particle compound into the nanofibers to obtain a composite fiber layer; a prepolymer formed by isocyanate and polyether glycol is subjected to chain extension and modified nano-silver reaction, an assistant is added to obtain a polyurethane protective layer emulsion, and the breathable dustproof wall cloth is prepared by thermocuring according to the sequence of the PET non-woven fabric, the composite fiber layer and the polyurethane protective layer. The air permeability of the wall cloth is synergistically improved by changing the variety and dosage of the fibers, adjusting electrostatic spinning parameters and adjusting the porosity of the nanofibers; by introducing a polyurethane protective layer and cooperatively using a particle compound, the hydrophobicity of the wall cloth is improved, and meanwhile, the dustproof performance is improved; by introducing the modified nano-silver, the antibacterial property of the wall cloth is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wall cloths, in particular to a breathable dustproof wall cloth and a preparation method thereof. Background Art

[0002] As people's living standards improve, their requirements for interior decoration and environment also increase, especially for wall decoration. In the past, people used paint to paint walls, but paint contains a lot of substances that are harmful to the human body and are not conducive to environmental protection; wallpaper is gradually widely used, but it will produce a lot of pollution during the manufacturing process, and after long-term use, it faces the problems of insufficient water resistance and poor air permeability; then, people began to use fabrics to decorate walls, but fabrics are expensive, difficult to bond well to the wall, and poor in air permeability and dustproof effect.

[0003] Wall cloth, also known as wall cloth, is usually made of cotton cloth as the base cloth, and printed or embossed on the base cloth. It can also be woven with large jacquard. The patterns used are mostly geometric and floral patterns, which are gradually accepted by people. However, most of the traditional cloth preparation methods in the prior art consume a lot of resources, and it is difficult to effectively guarantee the quality of each cloth in batch preparation. The existing cloth is usually woven from natural fibers, but the cloth made of natural fibers also has some imperfections. The mechanical strength of cotton cloth is not high, and the waterproof and breathable performance of the cloth is relatively general; and the prepared waterproof cloth sacrifices breathability and dustproof performance in order to be waterproof, resulting in poor comprehensive practicality of the cloth, further limiting the scope of use of wall cloth.

[0004] In the prior art, many modification measures have been made for the antibacterial properties of wall cloths. The antibacterial properties of wall cloths are improved by adding antibacterial agents or additives. However, the addition of additives has a great impact on the air permeability and dustproof properties of wall cloths. How to meet the high air permeability and high dustproof properties of wall cloths during use is a difficult problem that needs to be solved at present.

[0005] Therefore, a breathable dustproof wall cloth and a preparation method thereof are proposed. Summary of the invention

[0006] The invention aims to provide a breathable dustproof wall cloth and a preparation method thereof. The invention comprises the following steps: using cotton fiber, PET fiber and modified fiber to prepare nanofiber by electrostatic spinning, introducing a particle composite into the nanofiber to obtain a composite fiber layer; chain extension of a prepolymer formed by isocyanate and polyether diol, reaction of modified nanosilver, adding an auxiliary agent to obtain a polyurethane protective layer emulsion, and finally thermally curing the PET non-woven fabric, the composite fiber layer and the polyurethane protective layer to obtain the breathable dustproof wall cloth; improving the tensile properties and air permeability of the wall cloth by changing the fiber type and dosage; adjusting the porosity of the nanofiber by adjusting the electrostatic spinning parameters to improve the air permeability of the wall cloth; improving the dustproof performance of the wall cloth by using a particle composite formed by carbon nanotubes and nano-titanium dioxide; improving the hydrophobicity and dustproof performance of the wall cloth by introducing a polyurethane protective layer; and improving the antibacterial performance of the wall cloth by introducing modified nanosilver.

[0007] To achieve the above object, the present invention provides the following technical solutions: In one aspect, the present invention provides a method for preparing a breathable dustproof wall cloth, wherein the preparation of the breathable dustproof wall cloth comprises the following steps: S1: bonding one side of the composite fiber layer to the non-woven fabric layer, and drying to obtain a composite material; S2: coating the side of the composite material not bonded to the non-woven fabric with a polyurethane protective layer emulsion, and curing the surface to obtain a wall cloth composite; passing the wall cloth composite through a hot air drying furnace to obtain a breathable dustproof wall cloth; The composite fiber layer includes a composite of nanofibers and particles; The non-woven fabric layer is PET non-woven fabric; The polyurethane protective layer emulsion comprises isocyanate, a chain extender and modified nano silver.

[0008] Preferably, the preparation of nanofibers comprises the following steps: Dissolve 10-25 parts of cotton fiber, PET fiber and modified fiber in a mixed solvent of DMF and ethanol in a mass ratio of 3:2, stir at 50°C for 12 hours to obtain a transparent solution; add the transparent solution into a 10 ml medical disposable syringe, and prepare electrospun fibers by an electrospinning method; dry the electrospun nanofibers at 60°C for 6 hours to obtain the nanofibers.

[0009] Preferably, the modified fiber is selected from one of nylon fiber, hemp fiber, acrylic fiber and glass fiber; the mass ratio of cotton fiber to the PET fiber is 1-3:1-7.

[0010] Preferably, the injection rate of the electrospinning method is 5-15 μL / min; the receiving distance of the electrospinning method is 20-40 cm; and the voltage of the electrospinning method is 8-15 KV.

[0011] Preferably, the preparation of the composite fiber comprises the following steps: The particle complex was added into 100 mL of ethanol and ultrasonically dispersed for 30 minutes to obtain a dispersion; the nanofibers were cut into thin slices and immersed in the dispersion, ultrasonically treated for 10 minutes, and vacuum dried at 60° C. for 3 hours to obtain a composite fiber layer.

[0012] Preferably, the preparation of the particle composite comprises the following steps: The carbon nanotubes are soaked in an acetic acid solution and washed with deionized water to obtain treated carbon nanotubes; the treated carbon nanotubes are added to a 50% ethanol solution to obtain a dispersion; tetraethyl titanate is dissolved in anhydrous ethanol to obtain a dissolving solution; the acetic acid solution is added dropwise to the dissolving solution to obtain a titanium precursor solution; the dispersion is added to the titanium precursor solution, stirred and mixed evenly, and heated to react to obtain a composite; the composite is washed with deionized water and vacuum dried to obtain a particle composite; the mass ratio of carbon nanotubes to nano-titanium dioxide in the particle composite is 1-3:1-2.

[0013] Preferably, the preparation of the polyurethane protective layer emulsion comprises the following steps: Add polyether diol and isocyanate into a three-necked flask, heat it to 80°C, add dibutyltin dilaurate, and react for 2 hours to obtain a mixed solution; cool the mixed solution to 50°C, add a chain extender, and use acetone to adjust the viscosity of the system, and keep the temperature to react to obtain a polyurethane prepolymer; disperse 8-25 parts of modified nanosilver in anhydrous ethanol, and disperse at high speed to obtain a dispersed system; under nitrogen protection, slowly add the dispersed system into the polyurethane prepolymer, stir and mix evenly, and react to obtain a mixed system; add antioxidant 1010, silicone defoamer and acetone to the mixed system for dilution, stir and disperse, and filter to obtain a polyurethane protective layer emulsion.

[0014] Preferably, the isocyanate is selected from toluene diisocyanate, hexamethylene diisocyanate, and tridecafluoroisocyanate; the chain extender is 2,2-bis(4-hydroxyphenyl)hexafluoropropane mixed with 1,4-butanediol in a mass ratio of 1:1; and the -NCO / -OH molar ratio in the polyurethane prepolymer is 0.8-1.5:1.

[0015] Preferably, the preparation of modified nanosilver comprises the following steps: The modifier is dissolved in a 95% ethanol solution, the pH value of the system is adjusted with acetic acid, and the solution is stirred to obtain a silane coupling agent solution; nanosilver is slowly added into the silane coupling agent solution to react to obtain a modified system; the modified system is dried at 100° C. for 2 hours, and the modified nanosilver is ground to obtain the modified nanosilver; wherein the modifier is selected from one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, methacryloxypropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; and the mass ratio of the modifier to the nanosilver is 1:5-8.

[0016] On the other hand, the present invention provides a breathable dustproof wall cloth prepared by the method as described above, wherein the breathable dustproof wall cloth comprises a polyurethane protective layer, a composite fiber layer and a PET non-woven fabric layer from top to bottom; the thickness of the polyurethane protective layer is 4-5mm; the thickness of the PET non-woven fabric layer is 4-5mm; the thickness of the composite fiber layer is 3-4mm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses cotton fiber, PET fiber and modified fiber, utilizes the high air permeability of cotton fiber and PET fiber; the high strength effect of modified fiber, and prepares nanofiber through electrostatic spinning. Through the synergistic effect of multiple fibers, the tensile strength of the wall cloth is improved while maintaining its air permeability.

[0018] 2. The present invention prepares nanofibers through electrospinning. By changing the injection rate, receiving distance and voltage during the electrospinning process, adjusting the process parameters, controlling the fiber diameter, and increasing the fiber porosity, the air permeability of the wall cloth is improved under the synergistic effect of multiple fibers.

[0019] 3. The present invention introduces a particle complex on the surface of the nanofiber and utilizes titanium dioxide particles to be evenly distributed in the pore size of the nanofiber to improve the bonding stability between the particle complex and the nanofiber layer; at the same time, the carbon nanotubes provide more polar groups, thereby improving the bonding ability between the polyurethane coating and the composite fiber layer. During the curing process, a stable three-dimensional network structure is formed, further improving the dustproof performance of the wall cloth.

[0020] 4. The present invention introduces a polyurethane protective layer and utilizes a particle composite to improve the binding ability between the polyurethane protective layer and the composite cellulose. At the same time, fluorinated isocyanate is introduced into the preparation of the polyurethane protective layer to improve the hydrophobicity of the wall cloth while cooperating with the particle composite to improve the dustproof performance of the wall cloth.

[0021] 5. The present invention introduces modified nanosilver into the polyurethane protective layer, utilizes the addition of a modifier to improve the binding stability of nanosilver and polyurethane, and simultaneously forms more cross-linking sites during the curing process, which is beneficial to the formation of a three-dimensional network structure, thereby improving the antibacterial ability and increasing the dustproof performance of the wall cloth. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the structure of the breathable dustproof wall cloth designed for the present invention; Figure 2 This is a graph showing changes in tensile strength and air permeability of Example 1 and Examples 5-7 of the present invention.

[0023] In the figure: 1. PET non-woven fabric layer; 2. composite fiber layer; 3. polyurethane protective layer. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The KH-560 described in the present invention is 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, CAS: 2530-83-8; the KH-570 described is methacryloxypropyltrimethoxysilane, CAS: 2530-85-0; the KH-792 described is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, CAS: 1760-24-3; and the PET described is polyethylene terephthalate.

[0026] The present invention provides a breathable dustproof wall cloth and a preparation method thereof, such as Figure 1 As shown, the breathable dustproof wall cloth is composed of a PET non-woven fabric layer 1, a composite fiber layer 2, and a polyurethane protective layer 3. Figure 1 to Figure 2 , the technical solution is as follows:

[0027] Example 1 40 parts of cotton fiber, 60 parts of PET fiber and 25 parts of nylon fiber were dissolved in an organic solvent (DMF: ethanol = 3:2), stirred at 50°C for 12 hours to obtain a transparent solution; the transparent solution was added into a 10 ml medical disposable syringe, and the transparent solution injection rate was controlled at 10 μL / min using a No. 20 stainless steel flat needle. The distance from the spinneret to the receiving plate was maintained at 30 cm, a high voltage of 12 KV was applied to the needle, the temperature was controlled at 40°C, the relative humidity was maintained at 30% ± 5%, and the aluminum foil on the receiving plate was grounded to collect the injected electrospun nanofibers; the electrospun nanofibers were dried in a vacuum drying oven at 60°C for 6 hours to obtain nanofibers.

[0028] Add 50 parts of carbon nanotubes to a 10% acetic acid solution and soak for 3 hours, then wash with deionized water to obtain treated carbon nanotubes; add the treated carbon nanotubes to a mixed solution of 50% ethanol and water to obtain a dispersion; dissolve tetraethyl titanate in anhydrous ethanol to obtain a dissolving solution; add acetic acid solution dropwise to the dissolving solution at a rate of 2 drops per second to obtain a titanium precursor solution; slowly add 50 parts of the dispersion to 50 parts of the titanium precursor solution, stir at 100 r / min, mix evenly, heat the system to 80°C and react for 2 hours to obtain a composite; wash the composite with deionized water, and vacuum dry for 2 hours to obtain a particle composite; cut the nanofibers into 4×4 cm 2The particle complex is added to 100 mL of ethanol, and ultrasonically dispersed for 30 minutes to obtain a dispersion; the fiber sheet is immersed in the dispersion, and ultrasonically treated for 10 minutes to make the titanium dioxide nanoparticles evenly distributed in the pore size of the nanofiber, and vacuum dried at 60° C. for 3 hours to obtain a composite fiber layer; Dissolve 5 parts of KH-560 in 95% ethanol solution, adjust the pH of the system to 3 with acetic acid, and stir in a magnetic stirrer at 50℃ for 2h to obtain a silane coupling agent solution; slowly add 30 parts of nanosilver to the silane coupling agent solution, react at 50℃ for 2h to obtain a modified system; dry the modified system at 100℃ for 2h, grind for 30min to obtain modified nanosilver. After dehydration treatment at 100℃ for 2h, add 50 parts of polyether diol and 60 parts of toluene diisocyanate into a three-necked flask, heat to 80℃ and stir for 30min, add 2 parts of catalyst dibutyltin dilaurate, and react for 2h to obtain a mixed solution; cool the mixed solution to 50℃, add 300 parts of a mixture of 2,2-bis(4-hydroxyphenyl)hexafluoropropane and 1,4-butanediol (mass fraction of 2,2-bis(4-hydroxyphenyl)hexafluoropropane and 1,4-butanediol) The system viscosity was adjusted to 1:1), 20 ml of acetone was used to adjust the system viscosity, and the polyurethane prepolymer was prepared by heat preservation reaction for 30 minutes; 20 parts of modified nanosilver were dispersed in anhydrous ethanol, and dispersed for 30 minutes using a high-speed disperser to obtain a dispersion system; under nitrogen protection, the dispersion system was slowly added to 100 parts of the polyurethane prepolymer, stirred and mixed evenly at 50 rpm, heated to 60°C, and reacted for 2 hours to obtain a mixed system; 5 parts of antioxidant 1010, 1 part of silicone defoamer and 5 ml of acetone were added to 100 parts of the mixed system for dilution, and the mixture was dispersed by stirring at 200 rpm for 30 minutes, and filtered to obtain a polyurethane protective layer emulsion.

[0029] One side of the composite fiber layer is bonded to the PET non-woven fabric layer, and maintained in a vacuum drying oven at 120°C and 200Pa for 2 hours to obtain a composite material; the side of the composite material that is not bonded to the non-woven fabric is coated with a polyurethane protective layer emulsion by a roller coater, the temperature is raised to 80°C, and the curing reaction is performed for 2 hours to obtain a wall cloth composite; the wall cloth composite is dried in a hot air drying furnace at a drying temperature of 100°C and a drying time of 5 hours to obtain a breathable dustproof wall cloth.

[0030] Example 2-13 The preparation steps and parameter conditions are similar to those of Example 1, with the differences shown in Table 1.

[0031] Table 1 Air permeability test of Examples 1-13 and Comparative Examples 1-4

[0032] Comparative Example 1 The preparation steps and parameter conditions are the same as those of Example 1, except that no modified fiber is added.

[0033] Comparative Example 2 The preparation steps and parameter conditions are the same as those of Example 1, except that only cotton fiber is added.

[0034] Comparative Example 3 The preparation steps and parameter conditions are the same as those of Example 1, except that only PET fibers are added.

[0035] Comparative Example 4 The preparation steps and parameter conditions of Example 1 are referred to, except that the nanofibers are not prepared by electrospinning, but the fiber material is obtained by conventional warp knitting, weft knitting or knitting.

[0036] Example 14 Air permeability test The breathable dustproof wall cloths prepared in Examples 1-13 and Comparative Examples 1-4 were tested for air permeability using a constant differential pressure flow measurement method, and the air permeability of the samples was tested using a TQD-G1 air permeability tester. The air permeability test was performed in accordance with GB / T5453-1997 standard. The tensile strength of the wall cloths prepared in Examples 1-13 and Comparative Examples 1-4 was tested in accordance with ASTM D-50395. The test results are shown in Table 2. The changes in tensile strength and air permeability of Examples 1 and 5-7 are shown in Table 2. Figure 2 shown.

[0037] Table 2 Air permeability test of Examples 1-13 and Comparative Examples 1-4

[0038] The results in Table 2 show that the wall cloths obtained without adding modified fibers in Comparative Examples 1-3 have a significant decrease in tensile strength compared to Examples 1-13. The addition of cotton fibers and PET fibers can increase the fiber porosity of the wall cloth, and the electrostatic spinning fiber process can be used to improve the air permeability of nanofibers. However, the strength of cotton fibers and PET fibers is poor. During the electrostatic spinning process, the spinning success rate decreases due to the decrease in strength, which reduces the production efficiency. The introduction of modified fibers can increase the strength of the fibers and improve the overall mechanical properties of the wall cloth. The strength of the wall cloth obtained without using electrostatic spinning in Comparative Example 4 is less affected, but the air permeability of the wall cloth is significantly reduced. The porosity of the modified fibers can be increased during the electrostatic spinning process, and the fibers form an uneven pore size distribution, which further improves the air permeability of the wall cloth. The results of Examples 1-4 show that the use of high-strength modified fibers significantly improves the tensile strength of the wall cloth. However, due to the differences in solubility and compatibility of polymer fibers, the use of glass fibers reduces the solubility of the fiber solution, and the effective content of glass fibers in the modified fibers obtained by electrostatic spinning is The amount is low, which has a lower effect on the overall mechanical properties of the wall cloth and reduces the air permeability of the wall cloth; the results of Example 1 and Examples 5-7 show that with the increase in the amount of modified fiber, the tensile strength of the wall cloth gradually increases, but the air permeability shows a gradually decreasing trend. The introduction of excessive nylon fiber leads to a decrease in the compatibility of the modified fiber, and the binding force decreases during the curing process with the non-woven fabric, further reducing the mechanical properties of the wall cloth; the results of Example 1 and Examples 8-11 show that the change in the amount of cotton fiber and PET fiber has a significant effect on the mechanical properties and air permeability of the wall cloth; cotton fiber has high flexibility and air permeability, PET fiber has excellent strength and air permeability, and can improve compatibility with the non-woven fabric matrix, increase bonding strength, control the mass ratio of cotton fiber to PET fiber, and effectively maintain the high strength of the wall cloth while improving air permeability; the results of Example 1 and Examples 12-13 show that with the change in the ratio of organic solvents, the effect on tensile strength is small, but the increase in DMF improves the dissolution of cellulose, so that the air permeability of the wall cloth is significantly improved.

[0039] Examples 15-24 The preparation methods and parameter conditions are similar to those of Example 1, with the differences shown in Table 3.

[0040] Table 3 Parameter changes of Examples 15-24

[0041] Comparative Example 4 The preparation steps and parameter conditions of Example 1 are referred to, except that the nanofibers are not prepared by electrospinning, but the fiber material is obtained by conventional warp knitting, weft knitting or knitting.

[0042] Comparative Example 5 The preparation steps and parameter conditions are the same as those of Example 17, except that only DMF is used as the organic solvent.

[0043] Comparative Example 6 The preparation steps and parameter conditions are the same as those of Example 17, except that only ethanol is used as the organic solvent.

[0044] Example 25 Air permeability measurement The wall cloths prepared in Examples 15-24 and Comparative Examples 4-6 were tested according to GB / T 5453-1997 "Determination of Air Permeability of Textiles" using a YG461E-Ⅲ fully automatic air permeability meter; the pressure difference of the instrument was set to 100 Pa, and multiple parts of each fabric were tested, and the average of the test results of 5 times was taken. At the same time, the porosity of Examples 15-24 and Comparative Examples 4-6 was tested; the porosity of the nanofibers was determined by the weight method. First, the mass of the nanofibers in the dry state was measured, and then the nanofibers were immersed in ethanol for 1 hour, and the fully penetrated nanofibers were obtained after weighing. The masses of the dry nanofibers and the wet nanofibers were recorded as W1 and W2, respectively. The porosity (P) was calculated by the following formula: P=W2-W1 / ρV, where ρ is the density of ethanol and V is the volume of the nanofibers; the test results are shown in Table 4.

[0045] Table 4 Air permeability test of Examples 15-24 and Comparative Examples 4-6

[0046] The results of Comparative Example 4 show that the porosity of the nanofibers prepared without electrospinning is small, the diameter of the fiber material is relatively coarse, and the air permeability is significantly reduced; the nanofibers obtained using a single solvent in Comparative Examples 5-6 have low porosity and poor air permeability. Due to the high solubility of DMF in fibers, the fiber concentration content in the obtained fiber solution is high, the fiber diameter becomes coarser, the fiber porosity decreases, and the air permeability weakens; at the same time, the high boiling point of DMF does not completely evaporate the solvent during the receiving process, the fibers are easily adhered to each other, forming a dense film, and the air permeability is reduced; using ethanol as a solvent cannot fully dissolve the fiber material, thereby generating fiber particles, affecting the porosity of the nanofibers; the results of Examples 15-18 show that as the size of the needle model decreases, the air permeability shows a trend of gradually increasing. As the needle size decreases, the diameter of the obtained fiber material decreases, the idle rate increases, and the air permeability increases. However, too small a size leads to a decrease in the mechanical strength of the fiber material during the injection process, affecting the overall performance of the wall cloth. From the results of Examples 17 and 19-24, it can be seen that changes in the electrospinning parameters have a significant effect on the air permeability of the wall cloth. Too fast an injection rate leads to an increase in the fiber diameter, a decrease in the fiber porosity, and a decrease in air permeability. Extending the receiving distance allows the fiber to have enough time to solidify before reaching the collector, resulting in a higher porosity and better air permeability. Under high pressure conditions, the fiber stretching is enhanced, the diameter is reduced, and finer fibers are formed, further improving the porosity and increasing the air permeability. However, too high a voltage can cause the fiber to break, resulting in fiber structural defects, affecting the mechanical properties of the wall cloth.

[0047] Embodiment 26 Add carbon nanotubes to 10% acetic acid solution and soak for 3 hours, and wash with deionized water to obtain treated carbon nanotubes; add the treated carbon nanotubes to a mixed solution of 50% ethanol and water to obtain a dispersion; dissolve tetraethyl titanate in anhydrous ethanol to obtain a dissolving solution; add acetic acid solution dropwise to the dissolving solution, maintaining 2 drops / second, to obtain a titanium precursor solution; slowly add the dispersion to the titanium precursor solution, stir at 100 r / min, mix evenly, heat the system to 80°C and react for 2 hours to obtain a complex; wash the complex with deionized water, and vacuum dry for 2 hours to obtain a particle complex; the rest of the preparation is as shown in Example 17.

[0048] Embodiment 27 Add carbon nanotubes to 10% acetic acid solution and soak for 3 hours, and wash with deionized water to obtain treated carbon nanotubes; add the treated carbon nanotubes to a mixed solution of 50% ethanol and water to obtain a dispersion; dissolve tetraethyl titanate in anhydrous ethanol to obtain a dissolving solution; add acetic acid solution dropwise to the dissolving solution, maintaining 2 drops / second, to obtain a titanium precursor solution; slowly add the titanium precursor solution to the dispersion, stir at 100 r / min, mix evenly, heat the system to 80°C and react for 2 hours to obtain a composite; wash the composite with deionized water, and vacuum dry for 2 hours to obtain a particle composite; the rest of the preparation is as shown in Example 17.

[0049] Examples 28-30 refer to the preparation method and parameter conditions of Example 26, and the differences are shown in Table 5.

[0050] Comparative Example 7 The preparation method and parameter conditions are the same as those of Example 26, except that no particle composite is used.

[0051] Comparative Example 8 The preparation method and parameter conditions are the same as those of Example 26, except that only nano-titanium dioxide is added.

[0052] Comparative Example 9 The preparation method and parameter conditions are the same as those of Example 26, except that only carbon nanotubes are added.

[0053] Example 31 Dust-proof performance test The wall cloths prepared in Examples 26-30 and Comparative Examples 7-9 were tested for dustproof performance: 5g of dry dust was evenly sprinkled on the surface of the wall cloth samples, and the dust particle size was kept at 2.5μm-10μm. Then the samples were tilted 90° and the fan was blown for 1 hour. The mass of the sample before the experiment was recorded as M0, the mass of the dust was recorded as M1, and the mass after tilting was recorded as M2. The dust removal rate λ was calculated as: λ=(M0+M1)-M2 / M1; the test results are shown in Table 5.

[0054] Table 5 Test results of Examples 26-30 and Comparative Examples 7-9

[0055] From the results in Table 5, it can be seen that in Example 7, the dust-proof performance of the wall cloth obtained by treating the nanofibers with the particle composite is significantly reduced compared with Examples 26-30, the dust removal rate is low, and the dust is easily enriched on the surface of the wall cloth. At the same time, the electrostatic effect of the fiber further increases the adsorption performance of the dust on the surface of the wall cloth; Compared with Example 7, the dust removal rate of Examples 8-9 is significantly improved, which further illustrates that the addition of inorganic particles can effectively reduce the adsorption effect of the wall cloth on dust; From the results of Examples 26-27, it can be seen that since the particle size of the inorganic particles is very small, it can fill the tiny pores or roughness on the surface of the wall cloth, making the surface of the wall cloth smoother, and the smooth surface can reduce the adhesion of dust. At the same time, titanium dioxide particles are evenly distributed in the pore size of nanofibers to improve the bonding stability between the particle complex and the composite fiber layer. The introduction of carbon nanotubes provides more polar groups, which improves the bonding ability between the polyurethane coating and the composite fiber layer. During the curing process, a stable three-dimensional network structure is formed. Replacing the loading mode of carbon nanotubes and nano-titanium dioxide will further affect the overall bonding ability between the polyurethane protective layer and the composite fiber and reduce the dustproof performance. The polyurethane protective layer on the surface of the wall cloth is balanced with the inorganic particles on the surface, and the inorganic particles will not migrate and agglomerate in the composite fiber layer, further improving the dustproof effect of the wall cloth.

[0056] Embodiment 32 Dissolve 5 parts of KH-560 in 95% ethanol solution, adjust the pH of the system to 3 with acetic acid, and stir in a magnetic stirrer at 50°C for 2 hours to obtain a silane coupling agent solution; slowly add 30 parts of nanosilver into the silane coupling agent solution, react at 50°C for 2 hours to obtain a modified system; dry the modified system at 100°C for 2 hours, and grind for 30 minutes to obtain modified nanosilver.

[0057] 90 parts of polyether diol and 90 parts of diphenylmethane diisocyanate were dehydrated at 100°C for 2 hours, added to a three-necked flask, heated to 80°C and stirred for 30 minutes, 0.03mmol of catalyst dibutyltin dilaurate was added, and the mixture was reacted for 2 hours to obtain a mixed solution; the mixed solution was cooled to 50°C, a chain extender and 5ml of acetone were added to adjust the viscosity of the system, and the mixture was kept warm for 30 minutes to obtain a polyurethane prepolymer; the modified nanosilver was dispersed in anhydrous ethanol and dispersed for 30 minutes using a high-speed disperser to obtain a dispersed system; under nitrogen protection, the dispersed system was slowly added to the polyurethane prepolymer, stirred and mixed evenly at 50rpm, heated to 60°C, and reacted for 2 hours to obtain a mixed system; 5 parts of antioxidant 1010, 1 part of silicone defoamer and 5ml of acetone were added to 100 parts of the mixed system for dilution, stirred and dispersed at 200rpm for 30 minutes, and filtered to obtain a polyurethane protective layer emulsion.

[0058] Examples 33-39 Refer to the preparation method and parameter conditions of Example 32, with the differences as shown in Table 6.

[0059] Comparative Example 10 The preparation method and parameter conditions are the same as those of Example 32, except that no polyurethane protective layer is added.

[0060] Comparative Example 11 The preparation method and parameter conditions are the same as those of Example 32, except that after the particle composite is mixed with the polyurethane protective layer emulsion, it is directly impregnated and cured with the composite fiber.

[0061] Comparative Example 12 The preparation method and parameter conditions are the same as those of Example 32, except that no hot air drying furnace drying treatment is performed.

[0062] Example 40 Waterproof performance test The wall coverings prepared in Examples 32-39 and Comparative Examples 10-12 were tested for waterproof performance in accordance with GB / T 4745-2012 “Testing and Evaluation of Waterproof Performance of Textiles - Water Dipping Method”. A dustproof performance test was also performed with reference to Example 31. The test results are shown in Table 6. Among them, waterproof grade 2 is for preventing dripping when tilted at 15 degrees; grade 6 is for preventing strong water flow impact; grade 7 is for preventing short-term immersion in water; and grade 8 is for preventing long-term immersion in water.

[0063] Table 6 Test results of Examples 32-39 and Comparative Examples 10-12

[0064] The results in Table 6 show that the water resistance and dustproof performance of the wall cloth prepared without adding the polyurethane coating protective layer in Comparative Example 10 are significantly lower than those in the examples. The addition of carbon nanotubes and nano-titanium dioxide on the surface of the composite fiber improves the hydrophilicity of the wall cloth, and water droplets can form a relatively uniform film on the surface. By utilizing the "self-cleaning" effect of inorganic particles, moisture can be more easily separated from dust, reducing the adhesion of dust. However, the hydrophilicity exhibited reduces the water resistance of the wall cloth, and increases the difficulty of washing and handling the wall cloth; in Comparative Example 11, the particle composite and the polyurethane protective layer are simultaneously coated on the fiber surface, which is not conducive to the bonding ability of the polyurethane protective layer and the composite fiber. The shedding of the coating during long-term use further affects the comprehensive performance of the wall cloth; in Comparative Example 12, the dustproof performance is reduced by not using a hot air drying furnace for drying; in Examples 32-37, by adjusting the isocyanate Type and dosage: When using fluorinated isocyanate, the hydrophobicity gradually improves with the increase of dosage. However, the reduction of cross-linking sites during the curing process affects the formation of the three-dimensional network structure, showing a reduced dust-proof performance; the introduction of the polyurethane protective layer and the synergistic particle complex improve the dust-proof performance of the wall cloth. The low surface energy of the fluorinated isocyanate migrates to the surface of the wall cloth, which increases the contact angle of the wall cloth surface, making it less likely for dust to adhere. Gravity can take away more dust and improve the dust removal rate; the results of Examples 34 and 38-39 show that the introduction of fluorinated chain extenders can improve the hydrophobicity, but the dust removal rate is reduced. Due to the large amount of non-polar groups introduced, the cross-linking sites are reduced, the network structure is not rich during the curing process, and the dust adsorption capacity is increased; the use of 1,4-butanediol and 2,2-bis(4-hydroxyphenyl)hexafluoropropane in combination can further improve the hydrophobicity and dust-proof performance of the wall cloth.

[0065] Examples 41-48 refer to the preparation steps and parameter conditions of Example 34, with the differences shown in Table 7.

[0066] Comparative Example 13 The preparation steps and parameter conditions are the same as those of Example 34, except that no modified nanosilver is added.

[0067] Comparative Example 14 The preparation steps and parameter conditions are the same as those of Example 34, except that the nanosilver is not modified.

[0068] Comparative Example 15 The preparation steps and parameter conditions are the same as those of Example 34, except that modified nanosilver is added to the polyurethane coating as an additive.

[0069] Example 49 Antibacterial Performance Test The wall coverings prepared in Examples 41-48 and Comparative Examples 13-15 were tested for their antibacterial properties. Bacterial solutions of Staphylococcus aureus and Escherichia coli were prepared according to the GB / T 20944.3-2008 test method. The wall coverings were cut into 4 mm × 4 mm samples. After high-temperature sterilization, the samples were placed in the bacterial solution and oscillated at 25°C for 10 min to take samples. The antibacterial rate of the samples was calculated. The test results are shown in Table 7.

[0070] Table 7 Determination of antibacterial properties of Examples 41-48 and Comparative Examples 13-15

[0071] The results in Table 7 show that the antibacterial rate of the wall cloth prepared without adding modified nanosilver in Comparative Example 13 against Staphylococcus aureus and Escherichia coli is significantly reduced, and the addition of nanosilver can provide a higher antibacterial rate; however, the antibacterial performance of Comparative Examples 14-15 is improved compared with Comparative Example 13, but it is significantly reduced compared with Examples 41-48. Due to the addition of KH-560 as a modifier, the modified nanosilver reacts with polyurethane to stably combine the nanosilver between the protective layers, preventing the nanosilver from falling off during use, thereby reducing the antibacterial property. At the same time, more cross-linking sites are formed during the curing process, which is beneficial to the three-dimensional network structure. The antibacterial ability of the wall cloth is improved while the dustproof performance is increased; the results of Examples 41-45 and 47-48 show that with the increase of the amount of nanosilver used, the antibacterial performance of the wall cloth gradually increases and tends to be stable, however, the addition of excessive nanosilver will further reduce the mechanical properties of the wall cloth and the strength will decrease; the results of Examples 41 and 45-46 show that the change of the type of modifier affects the antibacterial performance of the wall cloth, and the use of a polar group silane coupling agent can make the modified nanosilver fully react with the polyurethane, and the cross-linking effect of the polar group is utilized during the curing process to form a stable three-dimensional network structure while improving the antibacterial performance of the wall cloth.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a breathable dustproof wall cloth, characterized in that: The preparation of the breathable dustproof wall cloth comprises the following steps: S1: bonding one side of the composite fiber layer to the non-woven fabric layer, and drying to obtain a composite material; S2: coating the side of the composite material not bonded to the non-woven fabric layer with a polyurethane protective layer emulsion, and curing the surface to obtain a wall cloth composite; passing the wall cloth composite through a hot air drying furnace to obtain a breathable dustproof wall cloth; The composite fiber layer includes a composite of nanofibers and particles; The non-woven fabric layer is PET non-woven fabric; The polyurethane protective layer emulsion comprises isocyanate, a chain extender and modified nano silver.

2. The method for preparing a breathable dustproof wall cloth according to claim 1, characterized in that: The preparation of the nanofibers comprises the following steps: Dissolve 10-25 parts of cotton fiber, PET fiber and modified fiber in a mixed solvent of DMF and ethanol in a mass ratio of 3:2, stir at 50°C for 12 hours to obtain a transparent solution; add the transparent solution into a 10 ml medical disposable syringe, and prepare electrospun fiber by electrospinning; dry the electrospun fiber at 60°C for 6 hours to obtain the nanofiber.

3. The method for preparing a breathable dustproof wall cloth according to claim 2, characterized in that: The modified fiber is selected from one of nylon fiber, hemp fiber, acrylic fiber and glass fiber; the mass ratio of the cotton fiber to the PET fiber is 1-3:1-7.

4. The method for preparing a breathable dustproof wall cloth according to claim 2, characterized in that: The injection rate of the electrostatic spinning method is 5-15 μL / min; the receiving distance of the electrostatic spinning method is 20-40 cm; and the voltage of the electrostatic spinning method is 8-15 KV.

5. The method for preparing a breathable dustproof wall cloth according to claim 1, characterized in that: The preparation of the composite fiber layer comprises the following steps: The particle complex was added into 100 mL of ethanol and ultrasonically dispersed for 30 minutes to obtain a dispersion; the nanofibers were cut into thin slices and immersed in the dispersion, ultrasonically treated for 10 minutes, and vacuum dried at 60° C. for 3 hours to obtain the composite fiber layer.

6. The method for preparing a breathable dustproof wall cloth according to claim 5, characterized in that: The preparation of the particle composite comprises the following steps: The carbon nanotubes are soaked in an acetic acid solution and washed with deionized water to obtain treated carbon nanotubes; the treated carbon nanotubes are added to a 50% ethanol solution to obtain a dispersion; tetraethyl titanate is dissolved in anhydrous ethanol to obtain a dissolving solution; the acetic acid solution is added dropwise to the dissolving solution to obtain a titanium precursor solution; the dispersion is added to the titanium precursor solution, stirred and mixed evenly, and heated to react to obtain a composite; the composite is washed with deionized water and vacuum dried to obtain the particle composite; the mass ratio of the carbon nanotubes to nano-titanium dioxide in the particle composite is 1-3:1-2.

7. The method for preparing a breathable dustproof wall cloth according to claim 1, characterized in that: The preparation of the polyurethane protective layer emulsion comprises the following steps: Add polyether diol and the isocyanate into a three-necked flask, heat it to 80°C, add dibutyltin dilaurate, and react for 2 hours to obtain a mixed solution; cool the mixed solution to 50°C, add the chain extender, and adjust the viscosity of the system with acetone, and keep the temperature to react to obtain a polyurethane prepolymer; disperse 8-25 parts of the modified nanosilver in anhydrous ethanol, and disperse at high speed to obtain a dispersed system; under nitrogen protection, slowly add the dispersed system into the polyurethane prepolymer, stir and mix evenly, and react to obtain a mixed system; add antioxidant 1010, silicone defoamer and acetone to the mixed system for dilution, stir and disperse, and filter to obtain the polyurethane protective layer emulsion.

8. The method for preparing a breathable dustproof wall cloth according to claim 7, characterized in that: The isocyanate is selected from one of toluene diisocyanate, hexamethylene diisocyanate and tridecafluoroisocyanate; the chain extender is a mixture of 2,2-bis(4-hydroxyphenyl)hexafluoropropane and 1,4-butanediol in a mass ratio of 1:1; the -NCO / -OH molar ratio in the polyurethane prepolymer is 0.8-1.5:

1.

9. The method for preparing a breathable dustproof wall cloth according to claim 7, characterized in that: The preparation of the modified nano silver comprises the following steps: The modifier is dissolved in a 95% ethanol solution, the pH value of the system is adjusted with acetic acid, and the solution is stirred to obtain a silane coupling agent solution; nanosilver is slowly added into the silane coupling agent solution to react to obtain a modified system; the modified system is dried at 100° C. for 2 hours, and the modified nanosilver is ground to obtain the modified nanosilver; wherein the modifier is selected from one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, methacryloxypropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; and the mass ratio of the modifier to the nanosilver is 1:5-8.

10. A breathable dustproof wall cloth prepared by the method of claim 1, characterized in that: The breathable dustproof wall cloth comprises a polyurethane protective layer, a composite fiber layer and a PET non-woven fabric layer from top to bottom.

Citation Information

Patent Citations

  • Nanofiber composite membrane and preparation method thereof

    CN104727016A

  • Absorbable pad

    CN107530208A

  • Composite protective film

    CN111410921A

  • High-moisture-absorption organic cotton blended fabric and preparation process thereof

    CN116479569A

  • High-elasticity textile fiber and preparation process thereof

    CN119411249A